Redistribution Through Public Employment : The Case of Italy - Danninger, Stephan (IMF Working Papers; Working Paper ;, 1999)
This paper examines the regional distribution of public employment in Italy and documents two sets of facts. The first is the use of public employment as a subsidy from the North to the less wealthy South. We calculate that about half of the wage bill in the South of Italy can be identified as a subsidy, with both the size of public employment and wage levels used as a redistributive device. The second set of facts concerns the negative effects of subsidized public employment on individuals' attitudes toward job search, education, and 'risk-taking' activities. We conclude that heavy reliance on public employment distorts incentives and discourages the development of market activities in the South.